2015
DOI: 10.1159/000432401
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Macular Degeneration: A Complementopathy?

Abstract: Age-related macular degeneration (AMD) is a progressive eye disease affecting many elderly individuals. It has a multifactorial pathogenesis and is associated with numerous environmental (e.g. smoking, light and nutrition) and genetic risk factors. A breakthrough in the mechanisms causing AMD is emerging; the involvement of the alternative pathway of the complement system appears to play a pivotal role. This has led to the statement that AMD is a disease caused by a hyperactive complement system, allowing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 83 publications
(127 reference statements)
1
25
0
Order By: Relevance
“…Therefore, PEG-400 may potentially impair the control that proteases exert on the complement system [ 30 ], thus contributing to the formation of the terminal complement. Hence, activation of the complement receptors on the RPE by PEG-400-upregulated C3 and C5 participates in the pathological lesions observed in the outer retina and Bruch’s membrane [ 31 ]. Upregulation of the complement system found here is in line with previous results in models of dry AMD [ 13 , 32 ], and is in agreement with the finding that mice lacking of CD46, a membrane cofactor protein that plays a key role in the complement alternative pathway [ 33 ], demonstrate spontaneous age-related degenerative changes in the retina, RPE, and choroid that are consistent with the cardinal features of human AMD [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PEG-400 may potentially impair the control that proteases exert on the complement system [ 30 ], thus contributing to the formation of the terminal complement. Hence, activation of the complement receptors on the RPE by PEG-400-upregulated C3 and C5 participates in the pathological lesions observed in the outer retina and Bruch’s membrane [ 31 ]. Upregulation of the complement system found here is in line with previous results in models of dry AMD [ 13 , 32 ], and is in agreement with the finding that mice lacking of CD46, a membrane cofactor protein that plays a key role in the complement alternative pathway [ 33 ], demonstrate spontaneous age-related degenerative changes in the retina, RPE, and choroid that are consistent with the cardinal features of human AMD [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that the pathogenesis of AMD is the result of a complex multifactorial interaction between metabolic, functional, genetic, and environmental factors. 5 With aging, intracellular residual bodies containing lipofuscin accumulate in RPE cells. 6 RPE cells express such materials that would normally be eliminated by the choriocapillaris; however, as RPE dysfunction progresses, it results in alterations in the permeability of Bruch’s membrane, which leads to an accumulation of extruded material (drusen) between the two layers.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Greater increases in complement protein plasma levels have been associated with advanced stages of AMD, leading to the hypothesis that complement activation may be correlated with disease progression as well. 45 , 46 There is weak evidence that genetic polymorphisms in CHF associated with AMD may lead to over-activity of complement. Scholl et al found that median plasma concentrations of CHF were not increased in patients with AMD, 47 whereas complement factor D (CFD) levels did, indicating that CFD may be a more promising target for AMD therapy than CHF.…”
Section: Complementmentioning
confidence: 99%